Sulwe - Nyong, O.lupita (USA, 2019)
Sulwe has the darkest skin in her family and in her school. She wishes for her skin to be lighter, but through a supernatural experience, she comes to love her dark skin color.
Keywords: family life; Juvenile Fiction